Compensatory canine angulation in angle class II and III patients - Busato, Mauro Carlos Agner [UNESP]; Mendonça, Marcos Rogério de [UNESP]; Pereira, Alex Luiz Pozzobon [UNESP]; Tondelli, Pedro Marcelo [UNESP]; Cuoghi, Osmar Aparecido [UNESP] (FapUNIFESP (SciELO), 2009)
Abstract: The aim of this study was to evaluate the occurence of compensation in mesiodistal axial inclinations of canines in skeletal malocclusions patients. The sample consisted of 25 Angle Class II, division 1 malocclusion (group 1) and 19 Angle Class III malocclusion patients (group 2). After measurement of dental angulations through a method that associates plaster model photography and AutoCad software, comparisons between the groups were performed by T-test for independent samples. Results showed that there was no statistically significant difference (p ≤ 0.05) between groups, when maxillary canine angulations were compared. Regarding the mandibular canines, there was a statistically significant difference in dental angulation, expressed by 3.2° for group 1 and 0.15° for group 2. An upright position tendency for mandibular canines was observed in the Angle Class III sample. This configures a pattern of compensatory coronary positioning, since the angulation of these teeth makes them occupy less space in the dental arch and consequently mandibular incisors can be in a more retracted position in the sagittal plane.
Keywords: Angle class II; Angle class III; Cuspid; Dental models; Malocclusion; Orthodontics; adolescent; adult; canine tooth; comparative study; human; malocclusion; odontometry; pathophysiology; periodontal disease; retrospective study; Adolescent; Humans; Malocclusion, Angle Class II; Malocclusion, Angle Class III; Odontometry; Retrospective Studies; Tooth Mobility; Young Adult